Advanced Reading Skills Using The Whole Language Approach With Interactive Powerpoint Media in Elementary Schools - Juraeba, Juraeba; Hamna, Hamna; Mustakim, Mustakim (Universitas Trunojoyo Madura, 2024)
This study was motivated by the lack of advanced reading skills among students, which is attributed to two aspects: teacher-related and student-related factors during the learning process. From the teacher’s perspective, there was insufficient attention to students' learning styles, a lack of implementing a 15-minute reading activity before lessons, and a tendency to deliver materials and explanations without utilizing any media during teaching. From the students’ perspective, it was observed that students often played during lessons and found reading less engaging. The aim of this research is to improve advanced reading skills using the whole language approach with interactive PowerPoint media. The research method employed was Classroom Action Research (CAR), conducted in two cycles. Data collection techniques included observation, tests, and documentation. The results showed an improvement in advanced reading skills after implementing the whole language approach with interactive PowerPoint media. During the first cycle, the results of advanced reading skills in the Indonesian language subject for Grade IV students at SDN Malangga showed a completion rate of 70% based on assessments conducted over three sessions. In the second cycle, the students' advanced reading skills improved, with the completion rate increasing to 90%. This demonstrates that the use of the whole language approach with interactive PowerPoint media can significantly enhance students' advanced reading skills.